Changes in health and social well-being in the COVID-19 clinically vulnerable older English population during the pandemic - Di Gessa, Giorgio (J Epidemiol Community Health, 2021)
BACKGROUND: People with specific health profiles and diseases (such as diabetes, lung and heart conditions) have been classified as ‘clinically vulnerable’ (CV) to COVID-19, that is, at higher risk of severe illness and mortality from COVID-19, and were targeted for shielding. However, there is as yet little evidence on how the pandemic and shielding impacted the health and social well-being of CV older people. METHODS: We used data from wave 9 (2018/2019) and the first COVID-19 substudy (June/July 2020) of the English Longitudinal Study of Ageing. Using logistic and linear regression models, we investigated associations between being CV and health and social well-being during the pandemic, while controlling for prepandemic levels of the outcome variables. We also explored the interactions between CV and age group (50s, 60s, 70s, 80+), and between CV and shielding. RESULTS: CV people were more likely to report worse health and social well-being outcomes during the pandemic, even taking into account prepandemic differences. However, changes in health were not uniform across different age groups, and CV respondents were generally at greater risks of deterioration in health and social well-being compared with those not CV in the same age group. CV respondents who were shielding reported worse outcomes compared with those not CV and not shielding. CONCLUSIONS: While policies focusing on shielding CV older people reduce rates of hospitalisation and death from COVID-19, policymakers should also pay attention to understanding and addressing the wider needs of this group if their long-term health and social well-being are not to be compromised.